2012
DOI: 10.1105/tpc.112.105254
|View full text |Cite
|
Sign up to set email alerts
|

The KEEP ON GOING Protein of Arabidopsis Regulates Intracellular Protein Trafficking and Is Degraded during Fungal Infection

Abstract: In plants, the trans-Golgi network and early endosomes (TGN/EE) function as the central junction for major endomembrane trafficking events, including endocytosis and secretion. Here, we demonstrate that the KEEP ON GOING (KEG) protein of Arabidopsis thaliana localizes to the TGN/EE and plays an essential role in multiple intracellular trafficking processes. Lossof-function keg mutants exhibited severe defects in cell expansion, which correlated with defects in vacuole morphology. Confocal microscopy revealed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
68
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(76 citation statements)
references
References 74 publications
(139 reference statements)
6
68
0
Order By: Relevance
“…2G). This corresponds to the reported extranuclear localization of KEG-GFP (Gu and Innes, 2011) and the localization of the interaction between KEG and ENHANCED DISEASE RESISTANCE1 (EDR1; Gu and Innes, 2012) and between KEG and ABI5 . Coexpression of NINJA-nGFP led to a nuclear signal (Fig.…”
Section: Keg Interacts Specifically With Jaz12supporting
confidence: 87%
See 1 more Smart Citation
“…2G). This corresponds to the reported extranuclear localization of KEG-GFP (Gu and Innes, 2011) and the localization of the interaction between KEG and ENHANCED DISEASE RESISTANCE1 (EDR1; Gu and Innes, 2012) and between KEG and ABI5 . Coexpression of NINJA-nGFP led to a nuclear signal (Fig.…”
Section: Keg Interacts Specifically With Jaz12supporting
confidence: 87%
“…ABA treatment, however, promotes KEG self-ubiquitination and degradation, leading to an increase in ABI5 levels (Liu and Stone, 2010). Intriguingly, in contrast to the nuclear ABI5 subcellular localization, KEG is present in the trans-Golgi network (TGN; Gu and Innes, 2011) and is proposed to be a regulator of post-Golgi trafficking, including the secretion of apoplastic defense proteins (Gu and Innes, 2012). However, when inactivating the RING domain of KEG or mutating a conserved Lys in ABI5, an interaction between KEG and ABI5 can be observed outside the nucleus in the cytoplasm and at the TGN .…”
mentioning
confidence: 99%
“…The localization patterns of ATL1 in both transient and stable expression systems mirror those of a typical plasma membrane protein that undergoes constitutive endocytic trafficking, such as BRI1 (Geldner et al, 2007;Geldner and Robatzek, 2008;Kleine-Vehn et al, 2008;Gu and Innes, 2012). Therefore, we conclude that ATL1 is a membrane-associated E3 ligase that constitutively cycles between the plasma membrane and TGN/EE and after internalization can follow a retrograde transport pathway to the MVB/LE and eventually to the lytic vacuole for turnover.…”
Section: Atl1 Undergoes Constitutive Internalization and Vacuolar Degsupporting
confidence: 51%
“…KEG plays a critical role in multiple intracellular trafficking processes, including vacuole biogenesis, targeting of membrane-associated proteins to the vacuole, and secretion of apoplastic proteins (Gu and Innes, 2012). Mutation of KEG specifically suppresses edr1-mediated resistance, but how KEG affects edr1-mediated defenses remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…KEG interacts with EDR1 and recruits it to the trans-Golgi network/early endosome (TGN/EE) vesicles (Wawrzynska et al, 2008;Gu and Innes, 2011). KEG regulates endomembrane protein trafficking and is degraded specifically in cells infected by powdery mildew (Gu and Innes, 2012). Recent work showed that EDR1 also interacts with ARABIDOPSIS TOXICOS EN LEVADURA1 (ATL1), an E3 ubiquitin ligase that positively regulates resistance and cell death.…”
Section: Introductionmentioning
confidence: 99%